Fabrication Of Two Dimensional Silicon Photonic Crystal - Sin, Yew Keong (2010)
Photonic crystals are materials with a periodicity in refractive index. When electromagnetic waves with a wide range of frequencies propagate through these materials, certain range of frequencies is prohibited. The prohibited frequencies are known as photonic bandgap. In this study, a two dimensional silicon photonic crystal is fabricated by microfabrication method. Electron beam lithography and etching process are important processes in this method. Hence, preliminary works on optimization parameters in electron beam lithography are necessary.